2020
DOI: 10.7554/elife.59616
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits attributed to 17α-estradiol, a lifespan-extending compound, are mediated through estrogen receptor α

Abstract: Metabolic dysfunction underlies several chronic diseases, many of which are exacerbated by obesity. Dietary interventions can reverse metabolic declines and slow aging, although compliance issues remain paramount. 17α-estradiol treatment improves metabolic parameters and slows aging in male mice. The mechanisms by which 17α-estradiol elicits these benefits remain unresolved. Herein, we show that 17α-estradiol elicits similar genomic binding and transcriptional activation through estrogen receptor α (ERα) to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 157 publications
(282 reference statements)
6
35
1
Order By: Relevance
“…Interestingly, both SHAM and OVX mice receiving 17α-E2 displayed similar body mass and adiposity levels as the SHAM CON group, thereby suggesting that 17α-E2 treatment elicits similar effects as endogenous estrogens (likely 17β-E2), yet is not particularly synergistic. This suggests 17α-E2 and 17β-E2 are likely competing for the same receptors in vivo, which we provide evidence for in other reports ( Mann et al, 2020 ). We also evaluated intra- (periovarian [POV]) and extra-peritoneal (inguinal [ING]) white adipose tissue (WAT) masses because a redistribution of lipid to ectopic sites occurs and intra-peritoneal WAT depots increase with aging ( Stout et al, 2014 ; Stout et al, 2017b ).…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Interestingly, both SHAM and OVX mice receiving 17α-E2 displayed similar body mass and adiposity levels as the SHAM CON group, thereby suggesting that 17α-E2 treatment elicits similar effects as endogenous estrogens (likely 17β-E2), yet is not particularly synergistic. This suggests 17α-E2 and 17β-E2 are likely competing for the same receptors in vivo, which we provide evidence for in other reports ( Mann et al, 2020 ). We also evaluated intra- (periovarian [POV]) and extra-peritoneal (inguinal [ING]) white adipose tissue (WAT) masses because a redistribution of lipid to ectopic sites occurs and intra-peritoneal WAT depots increase with aging ( Stout et al, 2014 ; Stout et al, 2017b ).…”
Section: Resultssupporting
confidence: 87%
“…17α-E2 has recently been shown to induce considerable benefits on healthspan and lifespan in male mice ( Harrison et al, 2014 ; Strong et al, 2016 ; Stout et al, 2017a ; Garratt et al, 2017 ; Mann et al, 2020 ; Garratt et al, 2018 ), although little benefit has been observed in females receiving the compound ( Garratt et al, 2017 ; Garratt et al, 2018 ). We have postulated that the lack of beneficial effects of 17α-E2 in females may be due to the high levels of endogenous 17β-E2, which may outcompete the less-potent 17α-E2 at estrogen receptors ( Mann et al, 2020 ). In this report we sought to determine if 17α-E2 could elicit beneficial outcomes on age-related phenotypes associated with ovariectomy in female mice, with a specific emphasis on bone loss.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations